Gamification Framework for Engagement Design Using Pls-Sem - Jaffar, Suhaila; Baharum, Aslina (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The study's goal is to look into the gamification framework. This research focuses on gamification in e-learning, particularly in early childhood education; the 'what' and 'how' gamification can promote e-learning. Gamification has become popular in the past few years of research in education and business marketing. Early childhood is when brain formation can set the foundation for learning later. The most common scenes are the need to develop a complete and generic framework from a new perspective and its application to different environments in areas such as education and training, business, government, health, and life-day. However, the developed gamification for the business process has suggested more work needs to be done in the gamification area. Even their design framework is yet to be tested and aimed to act as a foundation for future research. Thus, this study aims to develop a gamified framework for children’s engagement design. PLS-SEM was used to analyse the proposed framework. Results show that the framework demonstrates that emotional and social factors substantially link children's engagement. Among the emotions noticed in this research are enjoyment, amusement, and satisfaction. Further research is valuable to explore more possibilities in increasing sustainability and the long-term effects of one gamification learning tool.